2013
DOI: 10.2166/wh.2013.212
|View full text |Cite
|
Sign up to set email alerts
|

Water quality perceptions and willingness to pay for clean water in peri-urban Cambodian communities

Abstract: This paper studies household demand for improved water quality in peri-urban Cambodia, with particular attention paid to the influence of water quality on willingness to pay (WTP). Utilizing data from 915 household surveys, we analyze responses to a contingent valuation scenario using multivariate logit regression techniques that account for subjective perceptions of water quality.We estimate a mean household WTP for improved water quality of US$3 (roughly 1.2% of mean income) per month for households in this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
43
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 72 publications
(52 citation statements)
references
References 27 publications
4
43
0
2
Order By: Relevance
“…Our WTP estimates indicate that reaching 50% of the target population would require subsidies of up to 89% of retail for the pot filter with its container; the median bid in these low-income communities was 11% of the retail price. These low WTP figures have also been reported in previous research (Ahuja et al, 2010;Amrose et al, 2015) with revealed WTP studies almost always yielding lower numbers than stated WTP (Luoto et al, 2012;Ahuja et al, 2010;Kremer et al, 2009;Orgill et al, 2013). The development of less expensive alternatives is promising, however; we found that a generic disinfectant-coagulant would be as acceptable to consumers as PuR, indicating a potential market for a generic version of this type of HWTS technology.…”
Section: Conclusion and Discussionsupporting
confidence: 79%
“…Our WTP estimates indicate that reaching 50% of the target population would require subsidies of up to 89% of retail for the pot filter with its container; the median bid in these low-income communities was 11% of the retail price. These low WTP figures have also been reported in previous research (Ahuja et al, 2010;Amrose et al, 2015) with revealed WTP studies almost always yielding lower numbers than stated WTP (Luoto et al, 2012;Ahuja et al, 2010;Kremer et al, 2009;Orgill et al, 2013). The development of less expensive alternatives is promising, however; we found that a generic disinfectant-coagulant would be as acceptable to consumers as PuR, indicating a potential market for a generic version of this type of HWTS technology.…”
Section: Conclusion and Discussionsupporting
confidence: 79%
“…Many studies also employed CVM to quantify the benefits of nonmarketed environmental goods and attributes in such a way that they can enter directly into cost-benefit calculations predominantly in western, North American and East Asian advanced and developed countries (Carson et al 2010). The CVM methodology highlights diverse issues like improvements in water quality and sanitation (Howard et al 2010;Vörösmarty, et al 2010;Orgill et al 2013), valuing forestry (Canadell and Raupach 2008;Gelo and Koch 2012;Mason et al 2013), exposure to flood risk (Lantz et al 2012;Kellens et al 2013), wetland conservation (Yoon 2009;Kaffashi et al 2013;Turner 2013), offsetting carbon emissions and groundwater contamination, health economics (Georgiou and Turner 2012;Del Borghi et al 2013;Everard et al 2013;Andersson et al 2014), cultural economics (Carvalho et al 2010;Wicker et al 2012), transportation safety and economics (Hess et al 2012;Kristiansen 2013) and a wide range of environmental services (Ojeda et al 2008;Vo et al 2012).…”
Section: Contingent Valuation Methodsmentioning
confidence: 99%
“…Households' perceptions of the relative safety of a source were also found to be uncorrelated with the level of microbial contamination of water from that source. 7 Similar use and mixing of water from multiple sources appear to be common in many other areas. 38,39 Hence, the creation of the infrastructure needed to deliver safe water does not always result in safe drinking water for consumers at the point of consumption.…”
Section: Access Not a Guarantee Of Consistent Usementioning
confidence: 96%